The use of autologous mesenchymal stem cells in complications of diabetes mellitus, in particular diabetic retinopathy: inputs and insights - Manshuk Yeltokova; Zeinet Аkhmedyanova; Zhanna Bayanbayeva; Assel Khassenova; Kulchat Yermekova (National Scientific Medical Center, 2022)
The review provided reveals the analysis of the available scientific literature on the feasibility of using cellular technologies, such as, autologous mesenchymal stem cells (MSCs) for diabetic retinopathy treatment. The results indicated the viability of cellular technologies in clinical ophthalmology with respect to anatomical features and immune privilege of the organ of vision. Additionally, feasibility, safety, and optimization of pathogenetic therapy for MSC transplantation expands the prospect of their use in late complications of type 1 and type 2 diabetes mellitus, in particular, diabetic retinopathy.